2019
DOI: 10.18632/aging.102048
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin-mediated hair growth induction effect of 3,4,5-tri-O-caffeoylquinic acid

Abstract: The hair follicle is a complex structure that goes through a cyclic period of growth (anagen), regression (catagen), and rest (telogen) under the regulation of several signaling pathways, including Wnt/ β-catenin, FGF, Shh, and Notch. The Wnt/β-catenin signaling is specifically involved in hair follicle morphogenesis, regeneration, and growth. β-catenin is expressed in the dermal papilla and promotes anagen induction and duration, as well as keratinocyte regulation and differentiation. In this study, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 69 publications
2
46
0
Order By: Relevance
“…The WNT/β-catenin pathway has a critical role in regulating the hair cycle by promoting hair growth ( 35 ). β-Catenin is a key regulator of hair follicle growth, and it is reported to be the primary initiator of the anagen phase ( 36 ). SFRP2 has been reported to be involved in several cellular activities and biological processes via the down-regulation of β-catenin in nuclear translocation.…”
Section: Resultsmentioning
confidence: 99%
“…The WNT/β-catenin pathway has a critical role in regulating the hair cycle by promoting hair growth ( 35 ). β-Catenin is a key regulator of hair follicle growth, and it is reported to be the primary initiator of the anagen phase ( 36 ). SFRP2 has been reported to be involved in several cellular activities and biological processes via the down-regulation of β-catenin in nuclear translocation.…”
Section: Resultsmentioning
confidence: 99%
“…We identified procyanidin B2 in C. inophyllum extracts, which gives rise to other potential targets to consider for further study of the hair growth activity of the extracts. Sinapic acid [ 65 ] and 3,4,5-tri- O -caffeoylquinic acid [ 66 ] both promote hair growth via several factors, namely stimulation of β-catenin production. Coumaric and sinapic acids are both hydroxycinnamic acids, and coumaric acid was identified in all three ethyl acetate extracts of F. berteroana, C. inophyllum and B. pilosa ( Table 1 ), further pointing towards a potential Wnt/β-catenin target stimulation of hair growth of our extracts and fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our previous studies, we demonstrated that TCQA promoted hair regrowth and pigmentation in eight-weeks-old C3H male, human dermal papilla cells and human melanocytes via the upregulation of Wnt/β-catenin pathway and its target genes. TCQA upregulated pathways involved in skin and hair stem cell differentiation and the protein expression of CD34, known to be enhanced when melanocytes stem cells are differentiating [ 31 33 ]. On the other hand, TCQA triggered the differentiation of Human Neural Stem Cells (hNSC) via Bone Morphogenetic Protein (BMP) pathway and the induction of cell cycle arrest [ 27 ].…”
Section: Introductionmentioning
confidence: 99%